2023
DOI: 10.1002/jsfa.12910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin and genistein on egg quality, lipid profiles, and immunity in laying hens

Abstract: BACKGROUNDAfter the peak laying stage, laying hens become susceptible to lipid accumulation and inflammatory reactions. The objective of this experiment was to examine the impact of quercetin and genistein on egg quality and lipid profiles in laying hens. A total of 240 Hy‐line Browns were randomly assigned to three dietary treatments. Each treatment had eight replicates, with 10 hens in each replicate, and the hens were aged between 46 and 56 weeks. The test diets consisted of a corn‐soybean meal‐based basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…As previously reported, the effective concentration range of genistein supplemented in the normal chow diet of hens is 10 to 400 mg/kg ( Lv et al, 2019b ; Gao et al, 2021 ; Li et al, 2023 ). Moreover, our previous study demonstrated that feeding hens 40 mg/kg genistein was effective ( Lv et al, 2018b ; Wei et al, 2024 ). Therefore, we selected a dose of 40 mg/kg to assess the long-term effects of genistein.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, the effective concentration range of genistein supplemented in the normal chow diet of hens is 10 to 400 mg/kg ( Lv et al, 2019b ; Gao et al, 2021 ; Li et al, 2023 ). Moreover, our previous study demonstrated that feeding hens 40 mg/kg genistein was effective ( Lv et al, 2018b ; Wei et al, 2024 ). Therefore, we selected a dose of 40 mg/kg to assess the long-term effects of genistein.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, both quercetin and daidzein decreased the contents of TC and TG in the serum and liver, decreased the contents of LDL and VLDL in the serum, and increased the HDL content in the serum, which suggested that quercetin and daidzein improved lipid metabolism of layers. Studies have shown that dietary supplementation with flavonoids may regulate lipid deposition in the liver, enhance immunity, and improve egg quality of layers (48). Flavonoids may form insoluble complexes with cholesterol in digesta, thereby inhibiting the intestinal absorption of endogenous and exogenous cholesterol.…”
Section: E Ects Of Quercetin and Daidzein On Mda And Lipid Content In...mentioning
confidence: 99%